THREATS APPLIED IN THE NATIONAL SEGMENT OF THE INTERNET NETWORK - Gafurov Sh. A. (Galaxy International Interdisciplinary Research Journal, 2024)
In this article Threats and attacks directed at domains located in the national segment of the Internet network , levels of threats to web resources, existing vulnerabilities in web applications, and the interaction between an attack made as a result of this vulnerability and its possible consequences are presented.